Tectonic significance of the Carboniferous Big Pond Basin, Cape Breton Island, Nova Scotia - Bradley, Dwight C.; Bradley, Lauren M. (Canadian Journal of Earth Sciences, 1986)
Detailed mapping in southeastern Cape Breton Island has revealed a strike-slip origin for the small Carboniferous outlier at Big Pond. Topographically low Carboniferous sedimentary rocks occur between splays of a previously unrecognized, northeast-trending set of high-angle faults, the Big Pond fault system. The section is dominated by fanglomerates, which coarsen toward the faulted basin margins and which were deposited and (or) reworked by currents flowing toward the basin's center and along its axis. We interpret the fanglomerates as syntectonic. Interbedded limestones of Visean age (Windsor B Subzone) provide age control for the upper part of the 300 m section and, by inference, for at least some of the fault motion. Dextral motion on the Big Pond fault system is indicated by (1) slickenside stepping directions on minor faults, which juxtapose basement against basement and which parallel the main northeast-striking fault; (2) northeast-striking mesoscale faults within the basin, which produce dextral offsets; and (3) shear and extension fractures in fanglomerate clasts along the northeast-striking basin margin faults, which reveal dextral and down-to-basin motion. The location of the basin at a right step in the through-going dextral fault system implies that it is a pull-apart basin. We suggest that during Visean times, southern Cape Breton Island was cut by several such dextral wrench faults and associated sedimentary basins and that the tectonic climate was similar to that recognized by previous workers in Newfoundland and New Brunswick. No evidence was found in support of the paleomagnetically based hypothesis for sinistral strike slip during this time.